Transcriptomics and Fitness Data Reveal Adaptive Plasticity of Thermal Tolerance in Oysters Inhabiting Different Tidal Zones - Li, Ao; Li, Li; Wang, Wei; Song, Kai; Zhang, Guofan (Frontiers in Physiology, 2018)
Fine-scale adaptive evolution is always constrained by strong gene flow at vertical level in marine organisms. Rapid environmental fluctuations and phenotypic plasticity through optimization of fitness-related traits in organisms play important roles in shaping intraspecific divergence. The coastal systems experience strong variations in multiple abiotic environmental factors, especially the temperature. We used a typical intertidal species, Pacific oyster (Crassostrea gigas), to investigate the interaction between plasticity and adaptive evolution. We collected intertidal and subtidal oysters from two ecological niches and carried out common garden experiments for one generation. We identified fine-scale vertical adaptive divergence between intertidal and subtidal F1 progeny at both sites, based on different hierarchical phenotypes, including morphological, physiological, and molecular traits. We further quantified the global plasticity to thermal stress through transcriptomic analysis. The intertidal oysters exhibited slow growth rate. However, they showed high survival and metabolic rates under heat stress, indicating vertically fine-scale phenotypic adaptive mechanisms and evolutionary trade-offs between growth and thermal tolerance. Transcriptomic analysis confirmed that the intertidal oysters have evolved high plasticity. The genes were classified into three types: evolutionarily divergent, concordantly plastic, and adaptive plastic genes. The evolved divergence between intertidal and subtidal oysters for these gene sets showed a significant positive correlation with plastic changes of subtidal populations in response to high temperature. Furthermore, the intertidal oysters exhibited delayed large-scale increase in expressional plasticity than that in subtidal counterparts. The same direction between plasticity and selection suggests that the oysters have evolved adaptive plasticity. This implies that adaptive plasticity facilitates the oyster to adapt to severe intertidal zones. The oysters exposed to strong environmental variability are thermal tolerant and have high adaptive potential to face the current global warming. Our findings will not only provide new insights into the significant role of plasticity in adaptive evolution that can be extended to other marine invertebrates, but also provide basic information for oyster resources conservation and reef reestablishment.